ANALYSIS OF STUDENTS CRITICAL THINKING ABILITY ON DISTANCE LEARNING PHYSICS LESSONS SMA/MA CITY OF TANJUNGBALAI T.A 2020/2021 - Panjaitan, Heri Syahputra Azhar; Sabani, Sabani (UNIVERSITAS NEGERI MEDAN, 2021)
This study aims to determine the level of students' critical thinking skills in distance learning physics subjects using aspects of critical thinking skills according to Ennis. The method used is descriptive with a quantitative approach. The population in this study was all SMA/MA Tanjungbalai City. The research sample was taken by purposive sampling as many as 150 students of class X from 5 sample schools SMA/MA Tanjungbalai City. The research instrument is a test of critical thinking skills and a questionnaire. The critical thinking ability of SMA/MA students in Tanjungbalai City in the subject of straight-motion physics in distance learning is still low overall. The average test of students' critical thinking skills is 55,73 in the low category. With the average achievement of each aspect, namely 61,83 in the aspect of Elementary Clarification, 56,37 in the aspect of Basic Support, 53,60 in the aspect of Interference, 56,17 in the aspect of Advance Clarification, 50,67 in the aspect of Strategy and Tactics. Student responses to distance learning show that all respondents of SMA/MA Tanjungbalai On the aspect of access to the use of distance learning, students gave an average response of 70%, indicating that students still find it difficult to use the distance learning method applied. Understanding the material shows that learning occurs when 78% of students better understand the material in face-to-face learning, and 52% of students understand physical lessons through distance learning. The aspect of implementing distance learning shows that students' responses to the effectiveness of distance learning are weak, with an average response of 65%